2006
DOI: 10.1292/jvms.68.119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyaluronic Acid on Ca<sup>2+</sup> Influx, Lactate Dehydrogenase Activity, and Cyclic AMP Synthesis in Canine Ejaculated Sperm during <i>In Vitro</i> Capacitation

Abstract: ABSTRACT. The effects of hyaluronic acid, which comprises the cumulus intercellular matrix, on Ca 2+ influx, lactate dehydrogenase (LDH) activity, and cyclic AMP synthesis in canine sperm during capacitation was investigated. Ejaculated sperm were collected from 10 Beagle dogs and the sperm were incubated for 4 hr in Eagle's MEM containing 10 µg/ml of hyaluronic acid. The percentages of actively motile sperm, hyperactivated sperm (HA-sperm), acrosome-reacted sperm (AR-sperm), and sperm labeled with fluorescein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…) and hyaluronic acid (Kawakami et al. ) have been involved in various processes such as sperm capacitation and acrosome reaction (Yadav et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…) and hyaluronic acid (Kawakami et al. ) have been involved in various processes such as sperm capacitation and acrosome reaction (Yadav et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; Kawakami et al. ), 500 μg/ml for 6 h in porcine (Suzuki et al. ), 750 μg/ml for 2 h in mouse (Bakhtiari et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in the present study, there is no evident change in blood lactic acid. A recent study suggested that Ca 2+ flowing into the cytoplasm can improve the activity of LDH [13] . Therefore, the release of Ca 2+ by slowly degraded HAp is probably the cause of elevated LDH activity.…”
Section: Lactic Acid Concentration and Ldh Activitymentioning
confidence: 99%
“…It was reported that Ca 2+ influx into the cytoplasm of canine sperm induces an increase of LDH activity in sperm [27]. In addition, Ce also participates in a series of redox reaction through valence alteration between +3 and +4 in vivo, which results in a series of changes of biological functions [28].…”
Section: Activation Of Ln 3+ On Ldh In Vivomentioning
confidence: 99%